CFD simulation of nozzle characteristics in a gas aggregation cluster source. (July 2016) - Zhang, Lianhua; Shao, Jianxiong; Chen, Ximeng
Abstract: Computational fluid dynamics (CFD) simulation for the sharp-edged nozzle was made using the OpenFOAM source code. Jet dynamics characteristics for the gas stream from a sharped-edged nozzle are then simulated under two-dimensional and axisymmetric steady state condition. Gas and particle velocities in a jet are obtained under different input and boundary conditions to provide an insight into the jet characteristics. For the range of downstream distances considered, the results indicate that a jet is characterized by an initial rapid decay of the axial velocity at the jet center while the cross-sectional flow evolves toward a top-hat profile downstream. Numerical simulation of the free-jet expansion from six types of nozzles indicated that the flow fields had significant differences in the early stages of the expansion. The effects of nozzle geometry on the nanoparticles were investigated. Simulation results indicated that the geometry of nozzle affected the cluster penetration efficiency and beam diameter. The extent to which to the Brownian diffusion can affect the particle extraction from nozzle is investigated. Simulations have shown that the Brownian motion perturbs the clusters from the trajectories dictated by the carrier gas and increases the rate of cluster deposition on the nozzle. Highlights: Results for the velocity and pressure profiles of gas flow in a sharp-edged orifice are obtained. Acceleration of nanoparticles through the orifice is studied. Comparison of the penetrations and beam widths of nanoparticles between six types of nozzle is achieved. The effect of Brownian motion on the penetrations and beam widths of nanoparticles is investigated in six types of nozzle.